Total Synthesis of Metagenetriindole A and Deoxytopsentin. Issue 4 (9th February 2017) - Pon Sathieshkumar, P.; Nagarajan, Rajagopal
Abstract: Metagenetriindole A and deoxytopsentin are the fascinating bisindole alkaloids due to their potential biological activities viz; cytotoxic, antimicrobial, antiplasmodial, MRSA PK inhibition etc. and they were isolated from deep‐sea sediment metagenomic clone derived Escherichia coli fermentation broth and Mediterranean sponge Topsentia genitrix respectively. The unavailability of large quantity of these alkaloids could restrict their further biological findings. So a short and efficient method to produce these biologically active alkaloids is important. Environmentally benign and metal free syntheses of these alkaloids is reported. The total synthesis involves bisindole formation and self‐condensation‐cyclization strategy without using any protecting group. Abstract : Protecting group free short total synthesis of biologically important metabolites Metagenetriindole A and Deoxytopsentin from easy accessible and readily available starting materials is reported.